J MATERN CHILD HEALTH 2017
DOI: 10.26911/thejmch.2017.02.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Infant Formula Feeding in Infants Aged 0-6 Months in Sukoharjo, Central Java

Abstract: Background: Formula feeding in infants aged 0-6 months may increase the risk of morbidity and mortality. Formula feeding in Indonesia continues to increase from 15% in 2003 to 79.8% in 2013. To the best of the authors' knowledge no studies have been done that analyzed the effects of constructs in Theory of Planned Behavior (TPB) on formula feeding practice. This study aimed to analyze the factors influencing formula feeding practice among lactating mothers for their infants aged 0-6 months, using TPB constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…Maternal attitude toward formula feeding was one of the predictors of formula feeding. Mothers who had a positive attitude toward formula feeding were two times more likely to give formula milk to their babies compared to those who had a negative or neutral attitude toward formula feeding, which is consistent with studies conducted in Jimma (Abebe et al, 2019) and Sukoharjo, Central Java (Nuralita et al, 2017). This might be because a woman who has a positive attitude toward formula feeding is easily derived to initiate formula milk to their babies when they find well‐packaged formula milk at pharmacies and supermarkets (Yee & Chin, 2007).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Maternal attitude toward formula feeding was one of the predictors of formula feeding. Mothers who had a positive attitude toward formula feeding were two times more likely to give formula milk to their babies compared to those who had a negative or neutral attitude toward formula feeding, which is consistent with studies conducted in Jimma (Abebe et al, 2019) and Sukoharjo, Central Java (Nuralita et al, 2017). This might be because a woman who has a positive attitude toward formula feeding is easily derived to initiate formula milk to their babies when they find well‐packaged formula milk at pharmacies and supermarkets (Yee & Chin, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the absence of private breastfeeding or pumping areas in their workplace could be a reason for formula feeding. Contrary to this finding, a study conducted in Sokoharjo, Central Java, reported that working mothers had two times less chance of formula feeding their babies (Nuralita et al, 2017). The reason for this discrepancy might be due to the presence of a well‐established policy that supports breastfeeding at their workplace and the maternal experience of pumping breast milk and storing it for their babies before going to their workplace.…”
Section: Discussionmentioning
confidence: 81%
“…In other words, having a negative attitude toward formula feeding reduces the likelihood of formula feeding by 60%. The nding is consistent with studies conducted in Jimma (13) and Sukoharjo, Central Java (37). This could be due to a women who had a positive attitude could be easily derived to initiate formula milk to their babies when they found well-packaged formula milk at pharmacies and supermarkets (26).…”
Section: Discussionsupporting
confidence: 87%
“…Contrary to this nding, study conducted in Sokoharjo, Centarl Java reported that working mothers had 2 times less chance of formula feeding their babies (37). The reason for this discrepancy might be due presence of a well stablished policy that support breast feeding at their work place and also maternal experience of pumping a breast milk and storing for their babies before going to their workplace.…”
Section: Discussionmentioning
confidence: 75%
“…Karena konseling biasanya disediakan untuk wanita hamil, pasangan dan ibu kandung memiliki pemahaman yang relatif sedikit tentang keperawatan eksklusif. Pendapatan keluarga Penelitian (7) mengatakan bahwa keluarga berpenghasilan tinggi lebih cenderung menyediakan susu formula daripada keluarga berpenghasilan rendah, ibu dengan pendidikan tinggi lebih cenderung mencari pekerjaan dan pendapatan keluarga lebih tinggi, yang akan mendorong ibu lebih memilih pemberian susu formula daripada ibu berpenghasilan rendah. Pendapatan keluarga p = 0,014.…”
Section: Dukungan Keluargaunclassified